2002
DOI: 10.1111/j.1748-7692.2002.tb01070.x
|View full text |Cite
|
Sign up to set email alerts
|

DIET OF SOUTH AMERICAN FUR SEALS (ARCTOCEPHALUS AUSTRALIS) IN ISLA DE LOBOS, URUGUAY

Abstract: The diet of Arctocephalus australis was studied through fecal analysis, from September of 1995 to May of 1998, in Isla de Lobos (35°01′50″S‐54°53′00″W), Uruguay. A total of 539 scats analyzed indicated that the weakfish (Cynoscion guatucupa), the cutlasfish (Trichiurus lepturus), the anchoveta (Engraulis anchoita), the anchovy (Anchoa marinii), and cephalopods were the main prey consumed by these fur seals. Prey richness was higher during January. The diet of A. australis varied between years, apparently relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 23 publications
2
78
1
3
Order By: Relevance
“…Further, rarefaction is the only diversity measure that is sensitive to rare species and is unbiased by sample size (Magurran, 1988). In the analysis of temporal or interspecific diet patterns, the use of rarefaction represents a robust approach (Arim & Jaksic, 2005) that brings a better insight about diet patterns than diversity indices (Naya et al, 2002). Rarefaction involves the estimation of the expected richness for a series of subsamples from the prey abundance distribution (Gotelli & Graves, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, rarefaction is the only diversity measure that is sensitive to rare species and is unbiased by sample size (Magurran, 1988). In the analysis of temporal or interspecific diet patterns, the use of rarefaction represents a robust approach (Arim & Jaksic, 2005) that brings a better insight about diet patterns than diversity indices (Naya et al, 2002). Rarefaction involves the estimation of the expected richness for a series of subsamples from the prey abundance distribution (Gotelli & Graves, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Subsamples where constructed with individual fishes (Gotelli & Colwell, 2001) rather than with individual preys (e.g. Naya et al, 2002). For each rarefaction curve, sub-samples from one fish to the effectively observed fish number were taken and species richness retained.…”
Section: Discussionmentioning
confidence: 99%
“…They make significantly longer feeding trips during winter than in summer (Kirkman et al 2002), suggesting that suitable prey is to be found much further from the island during winter Kirkman et al 2002;Lea et al 2002a). Animals returning to the island from distant foraging grounds during winter would undoubtedly defecate at sea, leading to an inherent bias in the recovery of hard prey remains (Naya et al 2002;Staniland 2002).…”
Section: Seasonal Variationmentioning
confidence: 99%
“…An indirect method consists in studying diet composition (from stomach contents and scats) and analyzing the degree of overlap between sea lion prey preferences and commercial species of fish and other marine species. Food habits studies offer valuable information about biological interactions between sea lions and fisheries (Harwood and Croxall, 1988;Daneri and Carlini, 1999;Koen Alonso et al, 2000, Naya et al, 2002Szteren et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…South American sea lions feed on a wide variety of prey, mainly teleost fish, cephalopods, and crustaceans (Vaz-Ferreira, 1982;George-Nascimento et al, 1985;Koen Alonso et al, 2000, Trites andSoto, 2004 7 ), some of which are important to commercial fisheries (Daneri and Carlini, 1999;Koen Alonso et al, 2000, Naya et al, 2002Soto et al, 2004).…”
Section: Introductionmentioning
confidence: 99%